Empirical study of implementation direct instruction (DI) and behavioral intervention of the attention deficit hyperactivity disorder (ADHD) on their development linguistics skills: sufism perspective - Agus Sholikhin; Siti Nurjanah; Naila Rohmaniyah (Jurnal Konseling dan Pendidikan, 2025)
This research explores the influence of implementing the Direct Instruction strategy through a behavioral approach in developing the linguistic intelligence of ADHD students at East OKU State SLB and Kayuagung State SLB, using a qualitative approach with observation, interviews, and documentation, and data analysis carried out through data reduction, data presentation, drawing conclusions, and triangulation to ensure validity. The results show that the application of Direct Instruction has a positive impact on increasing linguistic intelligence, where structured delivery of material, concrete media, and systematic steps, including initial orientation, material delivery, reading practice, alphabet exercises as a multisensory approach, and structured and independent practice, help students develop listening, speaking, reading, and writing abilities. Observations and interviews show that teachers can help ADHD students focus attention, compose sentences, and socialize through body movements. Teachers emphasize patience, understanding students' shortcomings, and compassion to create a supportive and empathetic learning environment that motivates students, while factors such as teacher creativity, preparedness, and learning media influence the effectiveness of Direct Instruction. Overall, structured Direct Instruction supported by creative and prepared teachers can be an effective strategy for developing the linguistic intelligence of ADHD students.